DF Malan en die Hoër Kritiek - Brümmer, Vincent (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The primary aim of this paper is to bring to light an important unpublished paper from 1910 by Dr DF Malan on the so-called Higher criticism. My paper throws light on Malan’s own theological position as pupil of the Dutch Ethical theologian JJP Valeton. In the first part of my paper I try to explain the issues concerning Higher Criticism and to recount the context in which the paper was written. The second part of my paper contains the original (Dutch) text of Malan’s paper. The final part consists of an annotated bibliography of the debate about Higher Criticism in the Dutch Reformed Church in South Africa during the first three decades of the 20th century. This serves to situate Malan’s position within the context of the Dutch Reformed Church.